Galectin-3 Plays an Important Role in BMP7-Induced Cementoblastic Differentiation of Human Periodontal Ligament Cells by Interacting with Extracellular Components - Min-Jeong Choi; Tae Min You; Young-Joo Jang (Hindawi Limited, 2023)
Human periodontal ligament stem cells (hPDLSCs) contain multipotent postnatal stem cells that differentiate into PDL progenitors, osteoblasts, and cementoblasts. Previously, we obtained cementoblast-like cells from hPDLSCs using bone morphogenetic protein 7 (BMP7) treatment. Differentiation into appropriate progenitor cells requires interactions and changes between stem or progenitor cells and their so-called environment niches, and cell surface markers play an important role. However, cementoblast-specific cell surface markers have not yet been fully studied. Through decoy immunization with intact cementoblasts, we developed a series of monoclonal antibodies against cementoblast-specific membrane/extracellular matrix (ECM) molecules. One of these antibodies, the anti-CM3 antibody, recognized an approximate 30 kDa protein in a mouse cementoblast cell line, and the CM3 antigenic molecule accumulated in the cementum region of human tooth roots. Using mass spectrometric analysis, we found that the antigenic molecules recognized by the anti-CM3 antibody were galectin-3. As cementoblastic differentiation progressed, the expression of galectin-3 increased, and it localized at the cell surface. Inhibition of galectin-3 via siRNA and a specific inhibitor showed the complete blockage of cementoblastic differentiation and mineralization. In contrast, ectopic expression of galectin-3 induced cementoblastic differentiation. Galectin-3 interacted with laminin α2 and BMP7, and these interactions were diminished by galectin-3 inhibitors. These results suggested that galectin-3 participates in binding to the ECM component and trapping BMP7 to induce, in a sustained fashion, the upregulation of cementoblastic differentiation. Finally, galectin-3 could be a potential cementoblast-specific cell surface marker, with functional importance in cell-to-ECM interactions.